The role of resilience processes in education and well-being outcomes for separated children in Uganda: Exploring street-connected children's pathways through a resilience-based programme and beyond. Issue 1 (March 2022) - Edmonds, Ruth; Ochaya, Alfred; Sansom, Nicola
This article explores the role resilience processes play in education and well-being outcomes for street-connected children. It draws on research and practice undertaken as part of the Building with Bamboo Programme (BwB) on resilience. BwB investigated the forms a resilience-based approach might usefully take in practice, the effect this has on promoting resilience in children, and how this resilience leads to improved outcomes in their lives. Our article draws specifically on the experiences of street-connected children who were involved in such approaches as part of programmes at S.A.L.V.E. International, Uganda between 2016 and 2018. Drawing on individual street-connected children's resilience pathways through BwB and beyond, the article unpacks the connections between resilience processes and improved educational and well-being outcomes. It outlines how programme activities were developed and nurtured through cycles of learning and innovation to continually evolve existing strength-based programme practice with street-connected children whilst extending this work into the wider systems around children including peer networks, organisations, families and communities.